A multicenter phantom study on noise structure in [F-18] FDG-PET imaging. (September 2016) - Matheoud, Roberta; Lecchi, Michela; Lizio, Domenico; Isiaka, Babatunde; Scabbio, Camilla; Vigna, Luca; Rodella, Carlo; Indovina, Luca; Brambilla, Marco; Zoccarato, Orazio
Abstract : Introduction: Point-spread-function (PSF) modelling seem to be very attractive to obtain superior image quality in [F-18] FDG oncological studies, nonetheless it is known to significantly increase noise variability. Purpose: To evaluate the impact of PSF/TF on noise structure of iterative reconstructed (IR) images. Materials and methods: An anthropomorphic phantom with [F-18] FDG clinical concentrations was acquired on Biograph-mCT (Siemens) and Discovery690 (General Electric) PET/CT scanners. Overall, 96 datasets were obtained by varying reconstruction modalities (RM = IR, TF, PSF, TF+PSF), frame (128, 256), equivalent iterations number (IT = 63, 270), and Gaussian filter (GF = 2, 4, 6 mm). To limit noise correlation in PET imaging, 6 groups of concentric ROIs (r = 8;10;13;16;19 mm) were drawn on 3 slices at liver level. Fixing slice and ROI size, the signal variation was defined: SV% = 100∗SD/M, were SD, M are standard deviation, mean among the mean count values found for the ROIs, respectively. Results: SV decreases with ROI size and GF, and increases with IT. Moreover, SV depends on RM, but in different ways on the two PET scanners. For Biograph-mCT, highest and lowest SV were observed for PSF and TF and for GF = 2, 4, 6 mm mean(range) values were: 7.8%(5.1–10.6), 5.7%(3.1–8.5), 4.5%(2.5–6.7) and 4.5%(2.7–6.4), 3.8%(2.4–5.4), 3.2(2.2–4.5), respectively. For Discovery690, highest and lowest SV were observed for PSF+TF and IR and for GF = 2, 4, 6 mm the mean(range) values were: 8.3%(6.8–10.5), 8.1%(6.7–10.2), 7.9%(6.6–9.7) and 5.1%(3.5–8.2), 4.5%(3.1–7.0), 4.2%(3.2–6.2), respectively. Same trends are observed for the range of SV values. Conclusions: The PET scanners of this study showed different behaviors of SV in relation to RM. Increased SV could lead to degradation of precision in quantitative oncological studies with [F-18] FDG for monitoring treatment response.